1985
DOI: 10.1111/j.1476-5381.1985.tb08881.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective effects of thiol reagents on the binding sites for imipramine and neurotransmitter amines in the rat brain

Abstract: IThe action of the antithyroid drugs methimazole (MMI) and propylthiouracyl (PTU) on 4 The effects ofNEM on imipramine recognition sites and on the uptake of 5-HT could be prevented by DTT; protection was not obtained in other receptor systems.5 Three groups of receptors have been, thus, postulated, based upon their different sensitivity towards alterations in membrane [disulphide bridges = SHJ equilibrium: Group I, including imipramine recognition sites and the uptake system for 5-HT; Group II, including 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…There was no effect of hyperthyroidism on these uptake sites. In contrast, no change in 3H-IMI binding was seen in rats treated chronically with antithyroid drugs [42], However, in an another study [43], an increase in 3 H-IMI binding was reported following treatment with antithyroid agents.…”
Section: Discussionmentioning
confidence: 72%
“…There was no effect of hyperthyroidism on these uptake sites. In contrast, no change in 3H-IMI binding was seen in rats treated chronically with antithyroid drugs [42], However, in an another study [43], an increase in 3 H-IMI binding was reported following treatment with antithyroid agents.…”
Section: Discussionmentioning
confidence: 72%
“…This would obviously be a major constraint on flexibility of tertiary structure in this extracellular loop. However, in the case of the 5-HT transporter, treatment with thiol-reducing reagents increased both 5-HT transport and imipramine binding suggesting that a disulphide, if present, is not essential for activity (Biassoni and Vaccari, 1985;Biessen et al, 1988). Amara and Kuhar (1993) have commented on the distribution of proline residues in transporter proteins, there being conserved proline residues in five of the twelve transmembrane helices, and on their suggested roles of (1) induction of conformational change by realigning amphipathic helices after cis-trans isomerization of proline-containing peptide bonds, (2) binding pocket formation due to bending of transmembrane helices, and (3) hydrogen bonding through the more negative nature of carbonyl groups in proline-containing peptide bonds.…”
Section: General Considerations and Conclusionmentioning
confidence: 96%
“…The rather slow NEM modification observed in our laboratory and by Biassoni & Vaccari [21] and Davis [ZO] suggests that NEM might inactivate by alkylating an inert or hidden thiol group or by reacting non-specifically. In view of the data presented above we can exclude the latter.…”
Section: Volume 19mentioning
confidence: 92%
“…Chemical modification studies have revealed that the serotonergic [19][20][21], the GABAergic [22] and the noradrenergic reuptake systems [23] possess (di)thiols essential for ligand binding and activity. Blockade of the actual binding site by the respective ligands provides at least partial protection against thiol modification.…”
mentioning
confidence: 99%